TOWARDS INTERNATIONAL TEACHING OF INTERNATIONAL TEACHERS : The Role of Higher Education Libraries in the Management and Development of Institutional Repositories - BAKHTIYAR (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The research objective describes the role of higher education libraries in the development of institutional repositories. The research object is based on an analysis based on a detailed comprehensive study of the focus of content management discussion on the role of libraries in supporting the image of tertiary institutions through the development of institutional repositories to achieve the word class university. Research includes basic analysis based on and focuses on the main topic of the role of libraries in improving the image of tertiary institutions through the concept of an institution repository.Analyzing requires realistic critical thinking, applying conceptualization to the period, so that it is appropriate to do a historical approach, characterized by a realistic critical study of the development of a thought. Primary information sources are important components for primary data. Data collection utilizes library research through reading literature subjecting to the role of libraries and the development of institutional repositories. Analysis with qualitative descriptive analysis, sourced from a variety of reading material theoretical analysis, research and non-research. Research dominates describing, examining and evaluating factual facts to get solutions to problem solving contained in phenomena. In order to achieve validity, content analysis is needed, to analyze the meaning of important concepts, the role of libraries, repositories of higher education institutions. Observation of library activities, is used as an important component in supporting the construction of theory.The results of the study are the role of libraries in the development of tertiary institution repositories which are very urgent namely; (1). Attempts to manifest the publication of scientific works through a very wide network. (2). Having the same basic activities to realize the tri dharma of higher education. (3). Institutional repositories are both a challenge and an opportunity for libraries, because the competition for publication of scientific papers is very tight. (4). The webometric repository, as a webometric element, is a shared desire that Indonesia excels in the field of publication of scientific papers of international caliber. (5). Support the image of tertiary institutions in achieving university word class.